The Effect of Soy Milk (Glycine Max .L) and Guava Juice (Psidium Guajava. L) on Haemoglobin Levels in Anemic Female Adolescents - Lilia Faridatul Fauziah; Nabila Nurhidayah; Dian Ayu Ainun Nafies; Dwi Kurnia Purnama Sari (Universitas Airlangga, 2026)
Background: Anemia is a major public health concern in Indonesia, as evidenced by data from the East Java Provincial Health Office showing that 42% of female adolescents in East Java had anemia in 2020, and based on the Indonesian Health Survey (SKI) 2023, the national prevalence of anemia among female adolescents is approximately 15.5%. In specific regions, such as East Java, higher localized prevalence rates indicate that targeted nutritional interventions are still critically required. Female adolescents frequently have anemia as a result of insufficient nutritional intake and menstrual blood loss. Both pharmaceutical and non-pharmaceutical methods can be used to treat anemia. Objectives: The purpose of this study was to investigate the effect of soy milk (Glycine max L.) and red guava juice (Psidium guajava L.) on hemoglobin levels in anemic female adolescents as a non-pharmacological treatment. Methods: The quantitative study used a true experimental design with a two-group pre-test-post-test protocol. Purposive sampling was used to select 20 respondents, who were then divided into two treatment groups: soy milk and red guava juice. Hemoglobin levels were measured with the Easy Touch GCHb instrument and recorded on observation sheets. Data were analyzed using the paired sample t-test and the independent t-test. Results: Hemoglobin levels increased significantly before and after treatment in both the soy milk group (p=0.000) and the red guava juice group (p=0.004). The independent t-test yielded a p-value of 1.000 (p>0.05), indicating no significant difference between the two treatment groups. Conclusion: The findings show that both soy milk and red guava juice have a similar effect on increasing hemoglobin levels in anemic female adolescents.